2022
DOI: 10.1038/s41598-022-12763-8
|View full text |Cite
|
Sign up to set email alerts
|

Pinolenic acid exhibits anti-inflammatory and anti-atherogenic effects in peripheral blood-derived monocytes from patients with rheumatoid arthritis

Abstract: Pinolenic acid (PNLA), an omega-6 polyunsaturated fatty acid from pine nuts, has anti-inflammatory and anti-atherogenic effects. We aimed to investigate the direct anti-inflammatory effect and anti-atherogenic effects of PNLA on activated purified CD14 monocytes from peripheral blood of patients with rheumatoid arthritis (RA) in vitro. Flow cytometry was used to assess the proportions of CD14 monocytes expressing TNF-α, IL-6, IL-1β, and IL-8 in purified monocytes from patients with RA after lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Adipocyte function, glucose metabolism, insulin secretion signalling pathways, CCK secretion, mitochondrial ATP synthase, the NAD signalling pathway, and FA β-oxidation were among the metabolic signalling pathways identified. Ten miRNAs target PDK4, which controls TNF-α and NF-κB [5,88]; miR-3173, miR-2861, miR-626, miR-28, miR-7150, miR-3188, miR-879-5p, miR-393-5p, miR-708-5p, and miR-12118 [6]. Cellular metabolism depends on PDK4, and PDK4 deficiencies result in the death of hepatocytes by apoptosis with an increase in mitochondrial numbers, ROS production, prolonged activation of c-Jun N-terminal kinase (JNK), and decreased glutathione levels.…”
Section: Pnla and Modulation Of Mirnasmentioning
confidence: 99%
See 4 more Smart Citations
“…Adipocyte function, glucose metabolism, insulin secretion signalling pathways, CCK secretion, mitochondrial ATP synthase, the NAD signalling pathway, and FA β-oxidation were among the metabolic signalling pathways identified. Ten miRNAs target PDK4, which controls TNF-α and NF-κB [5,88]; miR-3173, miR-2861, miR-626, miR-28, miR-7150, miR-3188, miR-879-5p, miR-393-5p, miR-708-5p, and miR-12118 [6]. Cellular metabolism depends on PDK4, and PDK4 deficiencies result in the death of hepatocytes by apoptosis with an increase in mitochondrial numbers, ROS production, prolonged activation of c-Jun N-terminal kinase (JNK), and decreased glutathione levels.…”
Section: Pnla and Modulation Of Mirnasmentioning
confidence: 99%
“…Some PUFAs such as PNLA are examples of nutraceuticals which are believed to have anti-inflammatory effects through intracellular signals that activate anti-inflammatory pathways, such as peroxisome proliferator-activated receptors (PPARs) [ 4 , 5 , 6 ], and suppress pro-inflammatory pathways/mediators such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 5 , 6 ], arachidonic acid (AA)-derived eicosanoids, and reactive oxygen species (ROS) generation with generally an excellent safety profile [ 3 , 4 , 5 , 6 ]. Amr and Abeer showed that pine nuts oil (PNO) possesses a wide therapeutic effect, such as antibacterial, antifungal, antiviral, antiseptic, expectorant, cholagogue, choleretic, diuretic, and antihypertensive [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations